(untitled) (Journal of the College of Basic Education, 2023)
Picture is a term derived from a Latin word meaning imitation, and most of the ancient and modern uses of this term revolve around the same meaning, and then there are synonymous and close meanings for this term in the field of psychological use such as (*): similarity, copying, reproduction, the other image, either in In the Arabic language, the word image means the form of the verb, and as it came in Lisan al-Arab, I imagined the thing and imagined its image, so it was imagined for me.With the first steps of thinking, and with the first products of human interaction, the image had a presence, essential and a wonderful expression to embody man’s harmony with nature, and with the development of his symbolic capabilities, he had used the image not only to immortalize his civilization and make others feel his presence, but rather it was a kind of projection in his feelings towards ignorance By nature and his love for its assets, which he brought close to himself in a way close to the image.Thus, the image began to cover his vast ideas and wishes as equivalent to whatever he wanted to summon, from a place, tools, or people, and the formation of civilizations had given the image different dimensions of concerns, depending on the ecological component that surrounded this or that civilization, so the image was then active with the rocky nature Or sandy or muddy, and so on, civilizations were standing tall, and others laying back with no clues.